The Role of Darunnajah University Students in Creating an Islamic Society in Cibadung Village Dusun 3 Bulak Saga - Nurnaningsih; Calia Malsa (Jurnal Pengabdian Masyarakat (Bisma), 2023)
The Real Work Lecture (KKN) program provides significant benefits to the community, especially in terms of empowerment and regional development. Students can contribute in the form of dedication, potential development, and sustainable community empowerment. 23 days is relatively short, but in fact this KKN activity gives its own meaning to the students who carry it out. Intensive interaction with the community, including community leaders and villagers, makes them understand and will be better prepared when they enter the community. In the KKN process, students can also learn to develop social skills, leadership, and deepen understanding of cultural diversity and social problems faced by society. Therefore, the KKN program indirectly gives full responsibility to the KKN participants for providing services to the people of Cibadung Village and this is very beneficial for students, because researchers gain new knowledge and experience about how to socialize.